Air‐toxin technique: Introduction and analysis of effect using a photoimaging system. (14th February 2022) - Kang, Seung Hoon; Han, Yujin; Kim, Hei Sung
Abstract: Background: As an alternative to other approaches to facial rejuvenation, the air‐toxin technique (dermal injection of air with micro‐doses of botulinum toxin) is a promising method. We aimed to describe this novel technique and assess the overall safety and efficacy of the air‐toxin technique in facial rejuvenation. Materials and methods: A retrospective chart review was performed on cases treated with the air‐toxin technique. A total of 47 Korean patients underwent a single treatment session. Treatment efficacy was assessed objectively with serial VISIA ® (Canfield Scientific, NJ, USA) skin analysis data and subjectively based on the patients' assessment scores at Week 12. Results: A significant improvement in wrinkle ( p < 0.001), UV spot ( p < 0.001), and porphyrin ( p = 0.005) was objectively seen at 12 weeks follow‐up. Patients noted improvement in the categories wrinkle ( p < 0.01), redness ( p = 0.029), texture ( p < 0.001), dilated pore ( p < 0.001), and lifting ( p < 0.001) at Week 12 compared to baseline. No major adverse event was reported. Conclusions: Our data show that the air‐toxin technique is efficacious in facial rejuvenation as shown by improved skin analysis parameters and patient assessment scores. Notably, there was some discrepancy between the objective and subjective parameters of improvement.